Not sold here: limited access to legally available syringes at pharmacies in Tijuana, Mexico - Brouwer Kimberly C; Robles Brenda; Gallardo Manuel; Rosen Perth C; Pollini Robin A; Macalino Grace E; Lozada Remedios (BMC, 2011)
Abstract Background Sterile syringe access is a critical component of HIV prevention programs. Although retail pharmacies provide convenient outlets for syringe access, injection drug users (IDUs) may encounter barriers to syringe purchase even where purchase without a prescription is legal. We sought to obtain an objective measure of syringe access in Tijuana, Mexico, where IDUs report being denied or overcharged for syringes at pharmacies. Methods Trained "mystery shoppers" attempted to buy a 1 cc insulin syringe according to a predetermined script at all retail pharmacies in three Tijuana neighborhoods. The same pharmacies were surveyed by telephone regarding their syringe sales policies. Data on purchase attempts were analyzed using basic statistics to obtain an objective measure of syringe access and compared with data on stated sales policies to ascertain consistency. Results Only 46 (28.4%) of 162 syringe purchase attempts were successful. Leading reasons for unsuccessful attempts were being told that the pharmacy didn't sell syringes (35.3%), there were no syringes in stock (31.0%), or a prescription was required (20.7%). Of 136 pharmacies also surveyed by telephone, a majority (88.2%) reported selling syringes but only one-third (32.5%) had a successful mystery shopper purchase; the majority of unsuccessful purchases were attributed to being told the pharmacy didn't sell syringes. There was similar discordance regarding prescription policies: 74 pharmacies said in the telephone survey that they did not require a prescription for syringes, yet 10 of these pharmacies asked the mystery shopper for a prescription. Conclusions IDUs in Tijuana have limited access to syringes through retail pharmacies and policies and practices regarding syringe sales are inconsistent. Reasons for these restrictive and inconsistent practices must be identified and addressed to expand syringe access, reduce syringe sharing and prevent HIV transmission.